The core components of education 4.0 in higher education: Three case studies in engineering education. (July 2021) - Miranda, Jhonattan; Navarrete, Christelle; Noguez, Julieta; Molina-Espinosa, José-Martin; Ramírez-Montoya, María-Soledad; Navarro-Tuch, Sergio A.; Bustamante-Bello, Martín-Rogelio; Rosas-Fernández, José-Bernardo; Molina, Arturo
Highlights: The concept and vision of Education 4.0 in higher education are presented. Four core components are integrated to shape the proposed concept of Education 4.0: (i) Competencies, (ii) Learning Methods, (iii) Information and Communication Technologies, and (iv) Infrastructure. The components of Education 4.0 can apply to different educational levels and non-formal and informal educational environments. Three different case studies were presented to illustrate how current programs adopt the concept and vision of Education 4.0. Abstract: Technological progress and its rapid evolution have positively affected the industrial sector and different productive/service sectors. One of the service-sectors that have benefited the most has been Education. In this sector, the implementation of current and emerging technologies combined with innovative pedagogical procedures and best practices is known as Education 4.0, which, in this paper, is described and mapped according to the well-known periods of the four industrial revolutions and related to higher education. Likewise, four core components of Education 4.0 to be used as a reference for the design of new projects in educational innovation are proposed (i) Competencies, (ii) Learning Methods, (iii) Information and Communication Technologies, and (iv) Infrastructure. Finally, three case studies applied to Engineering Education illustrate how the proposed components are considered in educational programs' designs. Graphical abstract: Image, graphical abstract